(untitled) (Journal of Global Accounting, 2023)
This research has been carried out to examine small scale enterprises; challenges and prospects using Benin City as a case study. Small and medium scale enterprises plays a significant role in the growth and development of any nation due to their massive contribution to the economy. The sector is acknowledge to have huge potential for poverty alleviation, employment generation and wealth creation in any economy. Survey research design was adopted. Primary method of data collection were used, a well-structured questionnaire was designed and distributed to the fifteen (15) sampled water factories in Benin City. The questionnaire was the main research instrument used in the study. A questionnaire is a main document used which contains a set of questions used for soliciting information from respondents as the subject of a research investigation. A total number of 330 questionnaires were distributed out of which 300 were returned. Both descriptive and inferential statistic was used for the data analysis, frequency and percentages were used to analyze the section A of the questionnaire while multiple regression analysis was used for the test hypothesis. The result shows that poor, financing and shortages or unavailability of raw materials and epileptic power supply have a negative and significant effect on the small and medium scale enterprises in Benin City. We concluded that these challenges need to be looked into in other to help the small and medium scale enterprises for sustainability and necessary intervention should be provided. On the part of the government. We recommended that proper monitoring of agencies in charge of loans for SMEs should be put in place and business owners should have proper planning for their business for sustainability